(untitled) (Bangladesh Journal of Agricultural Research, 2016)
An experiment was conducted at the Horticultural Research Field of Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Salna, Gazipur during September 2008 to May 2009 to determine the response of hippeastrum (cu. Apple Blassom) to different combinations of nitrogen, phosphorus and potassium levels. There were 14 treatment combinations comprising four levels of nitrogen viz. 0, 100, 200, and 300 kgha-1; five levels of phosphorus viz. 0, 200,300, 400 and 500 kgha-1 and five levels of potassium viz. 0, 100, 200, 300 and 400 kgha-1 with an exclusively Cowdung treatment at the rate of 10 tha-1 . The experiment was laid out in a Randomized Complete Block Design with three replications. The growth and flowering parameter of hippeastrum were significantly influenced by combined application of N, P & K.The highest values in respect of leaves per plant (8.6), leaf breadth (5.4 cm), number of plants per bulb (3.07), flower scape per plant (2.07), flowers per scape (4.2), length and diameter of flower (14 cm x 13.83 cm), flower scape (43.33 cm x 29.37 cm) and flowering duration (10.7 days) were observed with N200P400K300. The same treatment showed earliness in days to flower scape emergence (172.3 days), days to flower bud appearance (185.3 days) and days to first flower open (189.3 days). The biggest flower (14.00 cm x 13.83 cm), longest flower scape (43.33 cm), maximum number of flowers per scape (4.20), and maximum flowering duration (11.5 days) were also exhibited by the treatment N200P400K300 .The control treatment (N0P0K0) recorded the lowest values except days to first leaf emergence, days to flower scape emergence, days to flower bud appearance and days to first flower open. Bangladesh J. Agril. Res. 41(1): 91-101, March 2016